Power series solution for 1st-order ODE

  • #1
I am trying to find the power series solution of

[tex]y' = x^2y[/tex]

but dont know how to arrive at the answer of [tex]y = a_0exp(x^3/3)[/tex]. [I know that it's an easily solved separable equation, I'm just trying to figure out how to find the power series solution]

My solution so far:

Assume
[tex] y = \sum_{n=0}^\infty a_nx^n [/tex]

then
[tex] y' = \sum_{n=1}^\infty na_nx^{n-1} [/tex]

giving:

[tex] \sum_{n=1}^\infty na_nx^{n-1} = x^2 \sum_{n=0}^\infty a_nx^n [/tex]
[tex] \sum_{n=1}^\infty na_nx^{n-1} = \sum_{n=0}^\infty a_nx^{n+2} [/tex]

changing the index for the LHS to give [tex]x^n [/tex]

[tex] \sum_{n=0}^\infty (n + 1)a_{n + 1}x^n [/tex]

changing the index for the RHS to give [tex]x^n[/tex]:

[tex] \sum_{n=2}^\infty a_{n - 2}x^{n} [/tex]

Then taking the first two terms out of the LHS sum, so that both sums start from the same point:

[tex] a_1 + 2a_2x + \sum_{n=2}^\infty (n + 1)a_{n + 1}x^n = \sum_{n=2}^\infty a_{n - 2}x^{n} [/tex]

I don't know what to do after this (I'm not entirely sure if what I've done so far is right, either).

If the y term in the initial equation didn't have the [tex]x^2[/tex] in front of it, it would be easy to equate the coefficients of [tex]x^n[/tex] to get the recursion formula. But having the terms [tex]a_1[/tex] and [tex]2a_2x[/tex] in front of the sum on the LHS throws me - can anyone explain clearly to me the correct steps required to solve the problem?
 
Last edited:

Answers and Replies

  • #2
MathNerd
We know that [tex]y'(0) = a_1[/tex] and [tex]y''(0) = 2 a_2[/tex]

We also know that [tex]y'(x) = x^2 \ y(x)[/tex] so that [tex]y'(0) = 0 = a_1[/tex]

Differentiating both sides we get [tex]y''(x) = 2x \ y(x) + x^2 \ y'(x)[/tex] and it is seen that [tex]y''(0) = 0 = 2 a_2[/tex] so now we know that [tex]a_1=a_2=0[/tex].

Hope this helps!
 
  • #3
MathNerd said:
We know that [tex]y'(0) = a_1[/tex] and [tex]y''(0) = 2 a_2[/tex]

We also know that [tex]y'(x) = x^2 \ y(x)[/tex] so that [tex]y'(0) = 0 = a_1[/tex]

Differentiating both sides we get [tex]y''(x) = 2x \ y(x) + x^2 \ y'(x)[/tex] and it is seen that [tex]y''(0) = 0 = 2 a_2[/tex] so now we know that [tex]a_1=a_2=0[/tex].

Hope this helps!

Thanks, that was a great help.
 

Related Threads on Power series solution for 1st-order ODE

  • Last Post
Replies
4
Views
4K
Replies
4
Views
197
Replies
1
Views
2K
  • Last Post
Replies
7
Views
2K
  • Last Post
Replies
3
Views
4K
  • Last Post
Replies
3
Views
6K
  • Last Post
Replies
2
Views
1K
  • Last Post
Replies
5
Views
2K
Replies
4
Views
2K
  • Last Post
Replies
2
Views
2K
Top